Impact of Project Based Learning (PjBL) on Creativity, Communication, and Adaptability among Engineering Students: A Journey from Classroom to Community for Sustainable Solutions - Nagamalla, Lavanya; Geedipally, Vanaja Reddy; Bandu, Uppaliah; Suryadevara, Gnanitha (Journal of Engineering Education Transformations, 2025)
This study examines how Project-Based Learning (PjBL) facilitates the development of sustainable projects and the impact of Project-Based Learning (PjBL) on creativity, communication, and adaptability among engineering students through a sustainability-focused project. The motivation for this research stems from the need to integrate sustainability in engineering education to address complex environmental challenges. The research was conducted at an engineering college in South India- Hyderabad Institute of Technology and Management (HITAM) where second-year Computer Science Engineering students participated in a composting project as part of their Environmental Science course. We investigated two hypotheses: 1) PjBL facilitates the development of sustainable projects, and 2) participation in sustainability-focused PjBL influences students’ creativity, communication, and adaptability. Data collection included qualitative feedback from farmers using the compost and a structured questionnaire to assess student skills. Findings indicated significant improvements in creativity, communication, and adaptability among students, and positive feedback from farmers regarding compost effectiveness. This study highlights the potential of PjBL in fostering essential skills and promoting sustainable practices in engineering education. Further research could explore broader applications and long-term impacts of PjBL in diverse educational contexts.